Protocolo de Enfermagem para Risco de Tromboembolismo em Oncologia - Veiga, Alessandro Gabriel Macedo [UNESP]; Santos, Izolete Aparecida Thomazini [UNESP]; Passeri, Celso Roberto; Papini, Silvia Justina [UNESP] (My University, 2015)
Venous thromboembolism (VTE) is a severe disease with high incidence worldwide, and, if it is not diagnosed early and properly treated, VTE can evolve and cause serious complications such as deep vein thrombosis (DVT) and pulmonary embolism (PE). We conducted an observational, descriptive and retrospective study to evaluate the medical records of patients with suspected deep venous thrombosis at Amaral Carvalho Hospital in 2011. For this study, the sample was 118 patients with suspected DVT, which were divided into two groups; G1, group of patients in clinical treatment and G2 the group of patients in surgical treatment, aged 04 91 years. Among these, thirtyeight patients were diagnosed with DVT confirmed by using UltrasoundDoppler (USDoppler) exam, considered as gold standard. Thus, the study contributes to the proposed protocol for the prevention of DVP in cancer patients.
Protocol for nursing thromboembolism risk oncology